From Osaka to the Gion: Vernacular Modernism in Kenji Mizoguchi’s Osaka Elegy (1936) and Sisters of the Gion (1936) - Paul Spicer (IAFOR Journal of Media, Communication & Film, 2017)
One of the most innovatory models for re-appraising the way in which popular cinema is able to articulate social and cultural change has been provided by Miriam Hansen’s idea of "vernacular modernism" (Hansen 2000). Hansen examines how cinema provided a popular, quotidian modernism in the context of western industrial influence upon East Asian culture. However, her definition does not explore the notion of vernacular as an embedded discourse, one which combines both traditional and modern forms. In an article entitled "Vernacular Culture" in the journal American Anthropologist, Margaret Lantis uses vernacular to connote "the culture-as-it-is-lived appropriate to well-defined places and situations" (1960: 205).